Construction of dye-stapled Quenchbodies by photochemical crosslinking to antibody nucleotide-binding sites. Issue 73 (31st August 2017) - Jeong, Hee-Jin; Matsumoto, Kenji; Itayama, Shuya; Kodama, Kozue; Abe, Ryoji; Dong, Jinhua; Shindo, Mitsuru; Ueda, Hiroshi
Abstract : We successfully converted an antibody and its variable region fragment to Quenchbodies, by photochemical crosslinking. Abstract : We successfully converted an antibody single-chain variable fragment and a full-sized antibody to Quenchbodies, which are a type of powerful fluorescent immunosensor, through ultraviolet-based photochemical crosslinking of an indole-3-butyric acid-conjugated fluorescent dye to the nucleotide-binding sites near the antigen-binding sites.